(untitled) (American Journal of Multidisciplinary Research and Innovation, 2024)
The intricate relationship between colors and memory has been a widespread interest in human psychology. The present study sought to better understand the influence of primary colors on memory retention among student gamers in Higher Education Institutions (HEIs). Applying a quantitative research approach, specifically an experimental research design, examined two independent variables and a control condition. Respondents were composed of 30 student gamers. Most of them were undergraduate students who were exposed to video game experiments and were chosen purposively. In analyzing the collected data, one-way ANOVA and Mauchly’s Test of Sphericity were utilized. Results revealed that primary colors do not significantly influence memory recall. This implies that better memory performance cannot be attributed to the facets of primary colors. Limitations were acknowledged regarding the chosen sample size and the research instruments’ procedural use. Hence, further studies may be conducted by minimizing the confounding variables and other external distractors in the same environment.